Potensi Jenis Bahan Pembawa (Carrier) Pemfiksasi N untuk Meningkatkan Pertumbuhan dan hasil Kedelai (Glycine max L.) pada Inceptisol Jatinangor - Suryatmana, Pujawati; Wati, Dyah Aditya; Kamluddin, Nadia Nuraniya; Setiawati, Mieke Rochimi (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
Sustainable agriculture is the proper solution for improving the fertility of Inceptisol, which is potentially suitable for soybean cultivation. Balanced fertilization, using both inorganic fertilizers and nitrogen-fixing biofertilizers, is one appropriate solution. To enhance the effectiveness of nitrogenfixing bacteria, a suitable carrier material is needed. This study aims to assess the potential of different carrier materials for Azotobacter and Bacillus on the growth and yield of soybeans on Inceptisol in Jatinangor. The research employs a Randomized Block Design with two factors: NPK dosage (0%, 50%, and 100%) and Azotobacter sp. and Bacillus sp. in various carriers (compost, bran, and Azolla powder) with 3 replicates. The results indicate that the interaction of Azotobacter sp. and Bacillus sp. in carriers had no significant effect on the height and chlorophyll content of soybean plants. The 100% NPK dosage yielded the highest number of pods compared to the 50% and 0% dosages. The treatment of Azotobacter and Bacillus in carriers did not significantly affect the number of filled pods, plant height, or chlorophyll content.